Factors Affecting the Purchase of Products through Online Applications by Students at Souphanouvong University - OUNPHOUVONG, stamy; LAYASAENG, Somyoth; KEODUANGKHAM, Phavone; SONESAI, Khamsone; PHONGVICHITH, Vannoula; MANYVANH, Jenny; SIPASERD, Salinda; PATHOUMVANH, Phoutthavong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study examines the demographic characteristics and purchasing behavior of Souphanouvong University students, focusing on their use of online applications for shopping. Data from 190 completed questionnaires reveal that the majority of respondents are female (57.7%) and aged 18-25 (81.5%), with an average monthly income below 1,600,000 kip. Facebook is the most commonly used platform for online shopping, and the most frequently purchased items are clothing and accessories. The study identifies key marketing mix factors influencing purchase decisions, including product diversity, ease of use, public relations on social media, and the availability of various payment methods. Regression analysis shows significant relationships between purchase decisions and factors such as gender, income, product quality, price, distribution channels, technology acceptance, safety, and marketing promotions. These findings highlight the importance of tailored marketing strategies to enhance online shopping experiences for university students.